A novel delivery system dextran sulfate coated amphiphilic chitosan derivatives-based nanoliposome: Capacity to improve in vitro digestion stability of (−)-epigallocatechin gallate. (March 2015) - Zou, Liqiang; Peng, Shengfeng; Liu, Wei; Chen, Xing; Liu, Chengmei
Abstract: A novel delivery system was developed by coating dextran sulfate (DS) on the surface of amphiphilic chitosan derivative nanoliposome (DCMC-NL) through electrostatic interaction. DS coated DCMC-NL (DS-DCMC-NL) exhibited larger average particle size, lower polydispersity index, and more negative zeta potential, compared with DCMC-NL. DS-DCMC-NL exhibited good in vitro digestion stability, with no obvious variations on particle size under gastrointestinal tract environment, while DCMC-NL immediately formed sediment after being mixed with simulated intestinal fluid (SIF). EGCG as a hydrophilic model drug was encapsulated in DS-DCMC-NL, with a high encapsulation efficiency (90.8%). EGCG loaded DS-DCMC-NL (EG-DS-DCMC-NL) exhibited a relative good sustaining release property. The degradation of EGCG during SIF was effectively slowed by the encapsulation with DS-DCMC-NL. This study expects to provide a promising carrier for further application of EGCG. Highlights: The cationic nanoliposome (DCMC-NL) was prepared using amphiphilic chitosan. A novel carrier was developed by coating dextran sulfate on DCMC-NL. The novel carrier exhibited good digestion stability during simulated intestinal fluid (SIF). DS-DCMC-NL exhibited a good (−)-epigallocatechin gallate (EGCG) sustaining release. EGCG stability in SIF was markedly enhanced by DS-DCMC-NL encapsulation.